2005
DOI: 10.1515/hf.2005.069
|View full text |Cite
|
Sign up to set email alerts
|

X-ray scattering studies of thermally modified Scots pine (Pinus sylvestris L.)

Abstract: Wood is thermally modified by heating and steaming in order to change its properties, e.g., to improve the biological resistance and to increase the hardness of wood. The structure of thermally modified Scots pine (Pinus sylvestris) was studied using wide-angle, small-angle and ultra-small-angle X-ray scattering methods. Modification temperatures varied from 100 to 240°C. No marked changes in the microfibril angle distribution were observed. The mass fraction of crystalline cellulose in wood (the crystallinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 22 publications
9
41
1
1
Order By: Relevance
“…Prior to the fitting, a linear background was subtracted from the intensity profiles. This was done by selecting regions on either side of the reflections, which were then used for the estimation of the background by a linear fit (Andersson et al 2003 Tables 1, 4) to values obtained from the respective large samples at the University of Helsinki by using a conventional X-ray diffractometer with known instrumental broadening (Andersson et al 2003(Andersson et al , 2005. The length and width of cellulose crystallites were calculated from all measured diffraction patterns.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the fitting, a linear background was subtracted from the intensity profiles. This was done by selecting regions on either side of the reflections, which were then used for the estimation of the background by a linear fit (Andersson et al 2003 Tables 1, 4) to values obtained from the respective large samples at the University of Helsinki by using a conventional X-ray diffractometer with known instrumental broadening (Andersson et al 2003(Andersson et al , 2005. The length and width of cellulose crystallites were calculated from all measured diffraction patterns.…”
Section: Methodsmentioning
confidence: 99%
“…Such a determination is useful to obtain structural information on a larger scale, which can then be used to compare different stems, growth conditions, treatments, etc. (Lindstrom et al 1998;Sarén et al 2001Sarén et al , 2004Vainio et al 2002;Andersson et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Some attention was paid to the relationship between thermal treatment and changes of structure. In particular, thermal expansion of the cellulose crystal lattice up to temperatures of about 250°C [10][11][12][13][14] and changes of crystallinity of various types of cellulose in the same temperature range was reported [15][16][17][18][19]. It was shown that annealing at temperatures of 270°C transform most of the cellulose Iα to the Iβ form [10].…”
Section: Introductionmentioning
confidence: 94%
“…Hemicellulose degradation lowers the hydroscopicity of wood (Korkut et al 2012). However, the hemicelluloses and lignin degradation increased the porosity of the wood cell wall, leading to a higher water absorption rate (Andersson et al 2005). This effect explains the insignificant WA reduction of the thermally modified wood compared with the control.…”
Section: Water Absorption (Wa) and Dimensional Stabilitymentioning
confidence: 98%
“…The degradation of the cell wall components increases the wood porosity (Andersson et al 2005), and the newly formed voids may increase the long-term water absorption. Moreover, thermal modification decreases the bending mechanical properties of wood significantly (Esteves and Pereira 2009).…”
Section: Introductionmentioning
confidence: 99%